The genus Octarrhena (Orchidaceae, Thelasiinae) in Vietnam with description of two new species - Averyanov, Leonid V.; Еskov Аlen K.; Truong, Ba Vuong; Nguyen, van Canh; Prilepsky, Nikolay G.; Nuraliev, Maxim S.; Maisak, Tatiana V.; Manh, Vu (Phytotaxa, 2020)
The genus Octarrhena (Orchidaceae) is distributed predominantly in Malesia and Papuasia. Its presence in eastern Indochina was uncovered as recently as in 2015 simultaneously with a description of O. minuscula from the Central Highlands of Vietnam. Here, we describe two more species of the genus, O. emarginata and O. perpusilla, also endemic to this mountain system. All three Vietnamese species of Octarrhena are local endemics with very limited allopatric distribution. We summarize the current knowledge on the genus in Vietnam and present a key for their identification, and a map with location of all known populations. Finally, we briefly discuss modern views on the worldwide species diversity of Octarrhena.